The Merck manual home health handbook - Porter, Robert S., 1950-; Kaplan, Justin A.; Homeier, Barbara P.; Merck & Co. (Whitehouse Station, NJ : Merck Research Laboratories, 2009)
A comprehensive health care resource provides information on the causes, symptoms, diagnosis, and treatment of almost two hundred diseases and disorders as well as health issues affecting men, women, children, and the elderly
Rev. ed. of: The Merck manual of medical information, home ed
Keywords: Medicine, Popular -- Handbooks, manuals, etc; Medicine -- Handbooks, manuals, etc; Diseases -- Handbooks, manuals, etc